2019
DOI: 10.32596/ejcm.galenos.2019.08.043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neonatal Hyperbilirubinemia on Ventricular Functions

Abstract: Objectives: Unconjugated hyperbilirubinemia is a common systemic disease in neonates. Many studies on etiology, risk factors, and treatment have been conducted, and guidelines have been established. Because unconjugated hyperbilirubinemia is a systemic disease, it affects the body, cells, cellular organelles, organs, and systems. Studies have also attempted to clarify the levels, mechanisms, and organs affected by unconjugated bilirubin. We aimed to investigate the effect of high unconjugated bilirubin levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Phototherapy Karabulut B et al 2019 [19] found no significant differences between the cases and controls in EF, FS, LVEDd, and LVEDs. They also discovered no statistically significant variations in mitral, tricuspid, septal E', A', and S' across groups.…”
Section: Discussionmentioning
confidence: 94%
“…Phototherapy Karabulut B et al 2019 [19] found no significant differences between the cases and controls in EF, FS, LVEDd, and LVEDs. They also discovered no statistically significant variations in mitral, tricuspid, septal E', A', and S' across groups.…”
Section: Discussionmentioning
confidence: 94%